The effect of leukocyte- and platelet-rich fibrin on the bone loss and primary stability of implants placed in posterior maxilla: a randomized clinical trial - Meshkat Naeimi Darestani; Hoori Asl Roosta; Seyed Ali Mosaddad; Siamak Yaghoubee (SpringerOpen, 2023)
Abstract Purpose In this study, we investigated the effects of leukocyte- and platelet-rich fibrin (L-PRF) on implant stability and alterations in the marginal bone surrounding posterior maxillary implants. Methods This randomized clinical trial was conducted to compare the variable of L-PRF placement around maxillary implants. Resonance frequency analysis (RFA) was used to evaluate the implant stability immediately after surgery and at 1, 2, 4, 6, 8, and 12 weeks after surgery (t 0 to t 6, respectively). In addition, the amount of marginal bone changes around the implant at t6 was compared with the baseline using periapical radiography. Results The RFA outcomes were statistically significant within each group (P < 0.001, Eta2 = 0.322); however, in none of the follow-ups and immediately after the surgery, there was a significant difference between the two groups in terms of the implant stability quotient (ISQ) scores (P > 0.05). At t0, the test and control groups' respective mean levels of marginal bone loss around the implants were 0.4836 mm and 0.7343 mm, significantly different from the corresponding values at t 6. On the other hand, marginal bone loss around the implant was not significantly different between the two groups in t0 and t6 (P = 0.532). Conclusions L-PRF did not improve the RFA outcomes of implants three months after implant placement, and changes in the ISQ values over time were the same in both groups. In addition, L-PRF had no superior effect on the marginal bone loss around the implants. Trial registration number: The research was registered in the Iranian Registry of Clinical Trials on 22 December 2020 (No: IRCT20200624047906N1), available at http://www.irct.ir